Effect of para-chlorophenylalanine on hormonal profile in anestrus buffaloes - SINGH, J K; LUDRI, R S (The Indian Journal of Animal Reproduction, 2008)
Parachlorophenylalanine (PCPA), when administered intra-peritoneally (I 00mg/kg body wt., 1/P) iseffective in reducing the level of prolactin(PRL) to certain extent by inhibiting serotonin biosynthesis in an estrusbuffaloes. 5-hydroxytryptophan (5-1 ITP) (I mg/kg/body wt., 1/M.) induces prolactin release by restoring serotoninbiosynthesis. Level of prolactin increased about three folds as compared to pre-treatment levels and more than1 O folds as compared to PRL level at 32 hr after PCPA treatment. These compounds have effect on cortisol levelof which showed fluctuations while as LH levels remain more or less unaffected. These compounds do notimprove anestrus condition in buffaloes
Keywords: Anestrus Buffalo; Parachlorophenylalanine; 5-hydroxytryptophan; prolactin; Cortisol; LH